ACUPRESSURE THERAPY TO DECREASE BLOOD PRESSURE FOR MRS. MT WITH CORONARY ARTERY DISEASE - Hanifah, Qolbu Ainun; Nurmansyah, Muhamad; Wirawan, Alfonsius Ade (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Background: The increase in cases of Coronary Artery Disease (CAD) is the highest compared to other cardiovascular diseases. Symptoms of CAD cause chest pain, increased heart rate, and increased blood pressure. Pharmacological therapy is sometimes resistant which ultimately fails to decrease blood pressure, thus introducing various non-pharmacological therapies, one of which is acupressure. The purpose of this study was to provide nursing care to CAD patients by applying acupressure to decrease blood pressure. The research method used was a case study on Mrs. MT with a descriptive approach based on caring for CAD patients. The application for acupressure was given on August 1-5 2024. The results showed significant changes in systolic and diastolic values. Acupressure is provided at points PC6, LI4, and LR3 once a day on average decrease systolic values while stabilizing diastolic values. Conclusion: Acupressure affects reducing blood pressure in CAD patients who have undergone Percutaneous Coronary Intervention (PCI).